FA05.02: AN ANALYSIS OF SURVIVAL TRENDS IN 471 PATIENTS AFTER ESOPHAGECTOMY FOR ESOPHAGEAL ADENOCARCINOMA. (14th September 2018) - Lada, Michal; Peyre, Christian; Wizorek, Joseph; Watson, Thomas; Peters, Jeffrey; Jones, Carolyn
Abstract: Background: Five-year survival after the surgical treatment of esophageal cancer has traditionally been reported to be as low as 15%. More recently, the improvement of clinical staging involving PET/CT and the introduction of neoadjuvant chemo-radiation have each altered the survival outcomes of patients with this lethal disease. The impact of these factors on survival trends has not been well described in literature. The aim of this study was to analyze the survival trends after esophagectomy for esophageal adenocarcinoma at a high-volume center. Methods: The study population consisted of 471 consecutive patients undergoing esophagectomy for esophageal adenocarcinoma at a university-based medical center between January 1, 2000 and July 31, 2017. Clinical variables were collected for three groups based on the date of esophagectomy and were compared (Group 1: 2000–2004, Group 2: 2005–2011, Group 3: 2012–2017). Survival was compared via the Kaplan-Meier (KM) method. Results: The 471 patients had a median age of 64.0 years (range 27.0–86.2) and 395/471 (84%) were male. Dysphagia (282/471, 60%), heartburn (63/471, 13%) and chest pain (29/471, 6%) were the most common presenting symptoms. The majority of the patients underwent transhiatal esophagectomy (n = 279, 59.1%) and en-bloc esophagectomy (n = 85, 18.0%). Staging with PET/CT was utilized in 316/471 patients (67%) with 6% of Group 1, 76% of Group 2 and 100% of Group 3, P < 0.001. Neoadjuvant therapy was utilized in 44% of patients, 209/357 (0% of Group 1, 45% of Group 2 and 76% of Group 3, P < 0.001). The median survival for the entire cohort was 30.0 months (range 0.3–208.0) with 5-year KM survival of 30% for Group 1, 43% for Group 2 and 47% for Group 3, P < 0.001, Figure. When comparing Group 1 and Group 2, the 10-year KM survival improved from 23% to 37%, P < 0.001. Conclusion: This analysis reveals an improvement in 5-year survival after esophagectomy from 30% to 47% over the past two decades. Similarly, 10-year survival has improved from 23% to 37%. The evolution of better clinical staging and advancements in neoadjuvant therapy likely played a vital role in these trends. In contrast to the earliest cohort, PET/CT is now routinely utilized in the staging of esophageal cancer. Further, other than those with early stage disease, all patients are currently evaluated for neoadjuvant chemo-radiation. Notably, the 5-year survival rate for the most recent cohort (2012–2017) approaches 50% and would likely be higher if patients with esophageal adenocarcinoma treated endoscopically were included. Improvements in staging and treatment paradigms for esophageal adenocarcinoma have resulted in significant progress towards cure. Disclosure: All authors have declared no conflicts of interest.